Synthesis and characterization of starch adipate nanoparticles from native sago strach - Goh, Donny Wah Ern (Universiti Malaysia Sarawak (UNIMAS), 2016)
This research aimed to synthesize and characterize physicochemical properties of starch adipate nanoparticles (SANPs). SANPs was synthesized by esterification reaction of native sago starch and adipic acid. The physical and chemical properties of SANPs were characterized. Throughout the screening of the esterification, with the condition temperature of 100°C and ethanol as precipitating media, gave the carbonyl group between starch and adipic acid. Different molar ratio of sodium hydroxide and adipic acid were used in synthesizing SANPs. The substitution of adipic acid onto starch chain was confinned by FTIR spectroscopy and the degree of substitution (DS) as determined by the back-titration method was within range of 0.004 - 0.366.